Which Neighborhood Matters? Estimating Multiple-Location Built Environment Effects on the Modality Style - Yaoxia Ge; Chen Gui; Yunqian Zhuang; Chaoying Yin; Wenyun Tang (Buildings)
The literature on the built environment (BE) and travel has offered evidence on both short- and long-term aspects of travel behavior with a main focus on home and work neighborhoods; however, the effects of the BE at the main activity space on the modality style have remained largely unknown. Moreover, little is known about the inter-modal substitutions and how the substitution is affected by the satiation effects. Based on survey data from Beijing, a Multiple Discrete Continuous Extreme Value (MDCEV) model is adopted to reveal the effects of BE at home, work, and activity space locations on the modality style. Results show that BE features at the home, work, and main activity space neighborhoods are essential triggers of the modality style, among which home BE features play the most vital role. The satiation effects visualized from various travel modes suggest that car traveling remains the most preferred travel mode. These findings can provide refined BE planning implications according to local land-use patterns for urban planners and transport policymakers because a one-size-fits-all design is not a solution to regulate people’s travel behavior.